HUBUNGAN REGULASI PASAR MODAL DENGAN ATRIBUT LABA: SUATU ANALISIS LINTAS NEGARA - Anggraini, Francisca Reni Retno (Jurnal Akuntansi dan Keuangan Indonesia, 2010)
The purpose of this paper is examining association between components of security market regulation which identified by LaPorta et al. (2006) and earnings attributes which identified by Francis et al. (2004). The sample are firms which are listed in stock exchange of 29 countries identified by LaPorta et al. (2006) with financial statement periods ended at December 3 P'. Seven groups of hypothesis regarding the association between characteristics of security market regulation and earnings attributes are suggested and tested using Rank Spearman Test. The results suggest strong association between the minor part of security market regulation components and earnings attributes, except the smoothness, value relevance, and timeliness earnings. This study find that there is non-linear correlation between earnings attributes and components °f security market regulation. This study gives two contributions. First, to the international accounting literature, this study extends prior studies (i.e. Ali and Wang 2000; Ball et al. 2000; and Boonlert-U-Thai et al. 2006) and it also confirms the prior studies (i.e. Francis et al. 2004; Hail and Leuz 2006; and Boonlert- U-Thai et al. 2006). Second, to the capital market regulator, this study shows the benefit of security market regulation in order to increase the quality of financial reporting.